Biosynthesis of Phenylnannolone A, a Multidrug Resistance Reversal Agent from the Halotolerant Myxobacterium Nannocystis pusilla B150. Issue 5 (13th February 2014) - Bouhired, Sarah M.; Crüsemann, Max; Almeida, Celso; Weber, Tilmann; Piel, Jörn; Schäberle, Till F.; König, Gabriele M.
Abstract The myxobacterial strain Nannocystis pusilla B150 synthesizes the structurally new polyketides phenylnannolone A–C. Apart from some common volatiles and siderophores, these are the first natural products from the genus Nannocystis. Phenylnannolone A shows inhibitory activity towards the ABCB1 gene product P‐glycoprotein and reverses daunorubicin resistance in cancer cells. To decipher the biochemical reactions leading to the formation of phenylnannolone A, the putative biosynthetic genes were identified (phn1, phn2). Phn2 is a polyketide synthase (PKS) with an NRPS‐like loading module, and its domain order is consistent with the phenylnannolone A structure. The functionality and substrate selectivity of the loading module were determined by means of a γ‐18O4‐ATP pyrophosphate exchange and a phosphopantetheine ejection assay. A specific activation of cinnamic acid by the AMP‐ligase was detected. Phn1 is a putative butyryl‐CoA carboxylase (BCC), providing ethylmalonyl‐CoA for the formation of the ethyl‐substituted part of phenylnannolone A. Phn1 is the first BCC found in biosynthetic genes for an ethyl‐substituted natural compound. Biosynthesis of phenylnannolone A, putatively encoded by phn1 and phn2, thus utilizes the first biosynthetic machinery in which both a BCC and a PKS are involved.